Selective chromium dissolution as an interfacial design strategy for enhanced oxygen evolution activity in CrFeCoNi oxy-carbide films - Tian Xiao; Koichi Yoshiyama; Kenji Yoshino; Tomohiro Higashi (Discover Electrochemistry)
Abstract High-entropy compounds have demonstrated remarkable electrocatalytic activity for oxygen evolution reaction (OER) in water. In this study, amorphous FeNi, CrFeNi, and CrFeCoNi oxy-carbide films were prepared using a single-step electrodeposition technique in an aqueous medium. Among them, CrFeCoNi films displayed outstanding electrocatalytic OER performance, achieving an overpotential of 315 mV at a current density (J) of 10 mA cm−2. At J of 50 mA cm−2, selective dissolution of Cr-species within CrFeCoNi was observed, which enhanced both electrocatalytic activity and stability of the film. This oxidative Cr dissolution process not only expanded the electrochemically active surface area but also facilitated the reoxidation of Fe, Co, and Ni, thereby weakening the binding strength of intermediates at catalytic sites. In addition, selective Cr dissolution improved the conductivity of the films owing to newly formed metal–metal bonding, promoting electron transfer and improving the OER performance, achieving an overpotential of 264 mV at J of 10 mA cm−2. This single-step electrodeposition approach and selective dissolution mechanism provide an effective pathway for the design and development of high-entropy compound-based electrocatalysts for efficient water electrolysis. Graphical Abstract